1988
DOI: 10.1590/s0074-02761988000100010
|View full text |Cite
|
Sign up to set email alerts
|

Redescription and resurrection from synonymy, of Aedes (Ochlerotatus) Rhyacophilus Costa Lima, 1933

Abstract: Aedes (Ochlerotatu) rhyacophilus Costa Lima i resurrected from the synonymy with Aedes (Ochlerotatus) scapularis (Rondani). Lectotype and paralectotypes are designated Larval, pupal and both sexes of adult stages are redescribed and illustrated. Bionomics include a picture of a brreding place. Diagnostic characters for distinguishing rhyacophilus from other species of the Scapularis Group are provided. Some data about known distribution are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Campos and Maciá (1998) brought that total number up to 211 species distributed within 20 genera. Probably some publications either had been lost or had not reached the authors in time-such as Sallum et al (1988); Rossi (1997);Rosa Freitas (1998) since the manuscript was submitted in 1997. Moreover, small errors in detail have been found in certain assignments-as one mistake subsequently corrected by Mitchell and Darsie (1985) with respect to Ps.…”
Section: Discussionmentioning
confidence: 99%
“…Campos and Maciá (1998) brought that total number up to 211 species distributed within 20 genera. Probably some publications either had been lost or had not reached the authors in time-such as Sallum et al (1988); Rossi (1997);Rosa Freitas (1998) since the manuscript was submitted in 1997. Moreover, small errors in detail have been found in certain assignments-as one mistake subsequently corrected by Mitchell and Darsie (1985) with respect to Ps.…”
Section: Discussionmentioning
confidence: 99%
“…Arnell [11] synonymized the species in 1976 under Aedes scapularis but did not mention the possibility for lack of an apical lobe. Sallum et al [42], resurrected and redescribed the species in 1988, clearly showing various differences from Arnell's description of Aedes scapularis, including but not limited to: The presence of posterior scutal fossal setae and achrostical setae, and the absence of a median stripe of pale scaling on the terga in the adult female; the lack of apical lobe of the gonocoxite in the adult male genitalia.…”
Section: Aedes Rhyacophilus Costa Lima 1933mentioning
confidence: 94%
“…In his work, he synonymized Aedes camposanus, Aedes hemisurus (together with Aedes indolescens), and Aedes (Ochlerotatus) rhyacophylus Costa Lima, 1933 under Aedes (Ochlerotatus) scapularis. Later, Aedes (Ochlerotatus) rhyacophylus was resurrected and redescribed in 1988 by Sallum et al [42], complete with a lectotype designation.…”
Section: The Evolution Of the Definition Of Ochlerotatus Scapularis (Rondani 1848)mentioning
confidence: 99%
See 1 more Smart Citation
“…Aedes scapularis is a species with vector competence for arboviruses and filarial worms (Lourenço-de-Oliveira & Deane, 1995; Rachou et al , 1995; Vasconcelos et al , 2001; Pauvolid-Corrêa et al , 2013), which belongs to the ‘Scapularis group’, a set of morphologically-related species such as Aedes rhyacophilus Costa Lima 1933 and Aedes serratus Theobald 1901 (Arnell, 1976; Sallum et al , 1988). Arnell (1976) reported that the claspette filament of male genitalia of Ae.…”
Section: Introductionmentioning
confidence: 99%